The Effect of Price and Free Shipping on Purchasing Decisions in E-Commerce Shopee on Students of The Faculty of Economics Pasim National University - Dahlan Ramdhani; Rahma Maulina (International Journal of Integrative Sciences, 2023)
This research was conducted on Pasim National University Faculty of Economics students who making purchases online on the Shopee platform. The research methodology applied in this study is a descriptive approach along with an associative approach. A total of 124 participants were sampled in this study, and the sampling technique used was stratified proportional random sampling. In addition, multiple linear regression analysis was also conducted, which involved t-test and f-test. Based on the results of the study, the independent variables (price and free shipping) show that there are factors that influence the dependent variable (purchasing decision) by 60.5%. The magnitude of the effect of the price variable on purchasing decisions is 16.3%, and the magnitude of the effect of free shipping on purchasing decisions is 44.1%. The implication of this research is that shopee can maintain price variations in order to compete with other e-commerce, also pay attention to product prices to match the quality provided and pay attention to providing free shipping without a minimum purchase so that consumers decide to buy in shopee e-commerce